Kinerja Keuangan dan Akuntabilitas Pengelolaan Dana Otonomi Khusus Sektor Pendidikan di Provinsi Papua - Agustinus, John (Universitas Brawijaya, Indonesia, 2011)
This study describes how the management of special autonomy fund education sector in the province of Papua. Total special autonomy funds received by the province of Papua is always rising. and in 2011 Papua Special Autonomy funds have S 1.2 Trillion of the fund in accordance with the special autonomy law, the Government Regulation no. 5 in 2006 determined that 30% is for the education sector. Special autonomy fund management problems of education sector in the province of Papua is so large that education funding in the province of Papua, but educational attainment for 10 years or during the era of special autonomy is not experiencing significant growth. It viewed the achievements of human development index provinisi papua for education is still low. The results provide a model of management of special autonomy fund for the education sector is to put more emphasis on capital expenditures, direct public expenditure for education sector in accordance with the mandate of the special autonomy law. perdasus no 1 of 2007, the government regulation No. 5 of 2006. Results achieved when the special autonomy fund management in accordance with the model of the direct management of capital expenditure is a significant educational achievement.